PENGARUH METODE LATIHAN VISUALISASI DAN PRAKTIK TERHADAP KECEPATAN RENANG GAYA BEBAS UMUR 10-13 TAHUN DI CSJ SWIMMING CLUB BANDAR LAMPUNG - Niko Petrik; Herman Tarigan; Muhammad Fajril Rifaldo; Lungit Wicaksono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of visualization and practice training on freestyle swimming speed at CSJ Swimming Club Bandar Lampung. The research method used was a comparative experiment. The sample used in this study was 30 athletes using the Ordinal Pairing technique. The instrument used was a 25m freestyle swimming speed test. The results of this study indicate that 1) There is a significant effect of the visualization and practice training treatment group on freestyle swimming speed, with the results of the t test at a significant level of 5% (0.05) obtained a t count value of 10,259> t table value = 2.160. 2) There is a significant effect of the non-visual group or without treatment on freestyle swimming speed, with the results of the t test at a significant level of 5% (0.05) obtained a t count value of 14,319> table value = 2.160. 3) There is a significant difference in the comparison test between the visualization and practice group and the non-visual group regarding freestyle swimming speed., with a 2-sided test data analysis (significant = 0.05) the calculated t value was 2.781 > t table = 2.048.